2015
DOI: 10.1007/s10585-015-9701-x
|View full text |Cite
|
Sign up to set email alerts
|

Ras suppressor-1 promotes apoptosis in breast cancer cells by inhibiting PINCH-1 and activating p53-upregulated-modulator of apoptosis (PUMA); verification from metastatic breast cancer human samples

Abstract: Metastasis, responsible for most deaths from breast cancer (BC), is a multistep process leading to cancer cell spread. Extracellular matrix (ECM)-related adhesion and apoptosis resistance play pivotal role in metastasis. Ras suppressor-1 (RSU-1) localizes to cell-ECM adhesions and binds to pro-survival adhesion protein PINCH-1. Little is known about the role of RSU-1 in BC. In the present study, we investigated the role of RSU-1 in BC metastasis using two BC cell lines that differ in terms of their metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 18 publications
3
37
1
2
Order By: Relevance
“…In accordance with the cell line data that suggested RSU-1 to be a negative regulator of PINCH-1, PINCH-1 expression showed dramatic reduction in BC samples both at the mRNA and protein level with statistically significant reduction in metastatic samples, in which RSU-1 was found to be elevated. Moreover, the assessment of the pro-apoptotic PUMA expression also confirmed findings in the cell lines showing an increase of PUMA expression in BC and metastatic samples in particular and a positive statistically significant correlation with RSU-1 expression in the same samples [43] . Therefore, RSU-1 should definitely be evaluated further as a potential metastasis biomarker in BC tissue samples.…”
Section: Ras Suppressor-1 (Rsu-1) In Metastasissupporting
confidence: 77%
See 2 more Smart Citations
“…In accordance with the cell line data that suggested RSU-1 to be a negative regulator of PINCH-1, PINCH-1 expression showed dramatic reduction in BC samples both at the mRNA and protein level with statistically significant reduction in metastatic samples, in which RSU-1 was found to be elevated. Moreover, the assessment of the pro-apoptotic PUMA expression also confirmed findings in the cell lines showing an increase of PUMA expression in BC and metastatic samples in particular and a positive statistically significant correlation with RSU-1 expression in the same samples [43] . Therefore, RSU-1 should definitely be evaluated further as a potential metastasis biomarker in BC tissue samples.…”
Section: Ras Suppressor-1 (Rsu-1) In Metastasissupporting
confidence: 77%
“…Interestingly, the data showed that RSU-1 mRNA expression was significantly increased in BC tissues when compared to normal adjacent tissue. Moreover, RSU-1 expression was significantly reduced in non-metastatic samples and significantly elevated in metastatic samples, clearly stating a different role of RSU-1 depending on the aggressiveness of the tumor, that could potentially lead to the use of RSU-1 as a novel biomarker of metastasis [43] . In accordance with the cell line data that suggested RSU-1 to be a negative regulator of PINCH-1, PINCH-1 expression showed dramatic reduction in BC samples both at the mRNA and protein level with statistically significant reduction in metastatic samples, in which RSU-1 was found to be elevated.…”
Section: Ras Suppressor-1 (Rsu-1) In Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…PINCH-1 promotes B-cell lymphoma (Bcl)-2-dependent survival signalling and inhibits c-Jun N-terminal kinase (JNK)-mediated apoptosis in the PrE (13). Although the function of PINCH remains unknown, increasing numbers and accumulating evidence indicates that PINCH has been correlated with cancer development, invasion and metastasis in malignant cells, including breast cancer (14), pseudomyxoma peritonei (15), gastric adenocarcinoma (16) and rectal cancer (17). For example, PINCH is demonstrated to protect tumor cells from apoptosis by increasing the activity of the pro-survival protein extracellular signal-regulated kinase (ERK)1/2 and Akt (18).…”
Section: Introductionmentioning
confidence: 99%
“…This result contradicts, at least in part, with the finding that Rsu1 stabilized PINCH1 29 , further complicating the functional relationship between PINCH1 and Rsu1.…”
Section: Pinch and Binding Partnersmentioning
confidence: 64%